O Exploring Health Literacy Perspectives Among Portuguese Community Pharmacists - Correia, Mónica; Espanha, Rita (Revista Española de Comunicación en Salud, 2025)
Introduction: HL is a broad concept that encompasses the knowledge, motivation and skills to access, understand, evaluate and apply health information and is a critical element for patient autonomy and improved outcomes in healthcare systems. Objectives: This study aims to explore Portuguese community pharmacists’ perspectives on health literacy (HL) and their role in improving it in patients. HL is becoming an even more relevant issue nowadays, as health systems are under increasing pressure due to longevity, lifestyles and environmental changes leading to new diseases. Methodology: A survey of 394 pharmacists across Portugal found that 96.95% recognise the importance of assessing patients’ HL. Results: The majority of pharmacists use a variety of techniques, such as screening questions and the teach-back method, to measure HL levels and adapt their communication. This is a key element in influencing patients’ health behaviour and improving their knowledge of their own health. Pharmacists also actively promote positive health behaviours and medication adherence, especially for non-communicable diseases. The findings underline the key role of pharmacists in improving HL, thereby contributing to better health outcomes and the sustainability of health systems.